2016
DOI: 10.5935/0103-507x.20160080
|View full text |Cite
|
Sign up to set email alerts
|

Use of biomarkers in pediatric sepsis: literature review

Abstract: Despite advances in recent years, sepsis is still a leading cause of hospitalization and mortality in infants and children. The presence of biomarkers during the response to an infectious insult makes it possible to use such biomarkers in screening, diagnosis, prognosis (risk stratification), monitoring of therapeutic response, and rational use of antibiotics (for example, the determination of adequate treatment length). Studies of biomarkers in sepsis in children are still relatively scarce. This review addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 67 publications
3
51
0
6
Order By: Relevance
“…current knowledge of PCT levels to predict blood culture results is scarce, especially in children (12)(13). A 2015 meta-analysis showed that PCT is highly accurate in differentiating bacterial and viral meningitis in children with 96% sensitivity (12). In our study included 311 consecutive patients, over a 7-year study period, PCT was effective to predict blood-culture results in cases that underwent a sepsis episode, particularly in immunocompromised children.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…current knowledge of PCT levels to predict blood culture results is scarce, especially in children (12)(13). A 2015 meta-analysis showed that PCT is highly accurate in differentiating bacterial and viral meningitis in children with 96% sensitivity (12). In our study included 311 consecutive patients, over a 7-year study period, PCT was effective to predict blood-culture results in cases that underwent a sepsis episode, particularly in immunocompromised children.…”
Section: Discussionmentioning
confidence: 65%
“…Although PCT as a biomarker for sepsis has been described in previous studies. current knowledge of PCT levels to predict blood culture results is scarce, especially in children (12)(13). A 2015 meta-analysis showed that PCT is highly accurate in differentiating bacterial and viral meningitis in children with 96% sensitivity (12).…”
Section: Discussionmentioning
confidence: 99%
“…Другой провоспалительный цитокин -ИЛ-8 яв-ляется мощным хемоаттрактантом и индуцирует активацию нейтрофилов [9,18]. На высокую диа-гностическую ценность повышенных величин ИЛ-6 и ИЛ-8 указывается в проведенных метаанализах по оценке роли этих цитокинов в диагностике неона-тального сепсиса [19,20]: высокие значения уровня ИЛ-8 ассоциируются с рисками развития не толь-ко самого сепсиса, но и в целом неблагоприятного исхода заболевания [21].…”
Section: перинатология и неонатологияunclassified
“…Since the clinical signs of sepsis in neonates are very subtle and nonspecific, predictive biomarkers are needed, particularly in economically developing countries, where the incidence, morbidity, and mortality of early neonatal sepsis (ENS) (sepsis diagnosed less than 72 h after birth) are particularly high. Evidence published to date is still far from convincing the physician to use procalcitonin as a biomarker for routine use in clinical practice as a risk stratifier and a prognostic predictor or even to guide the duration of antibiotic treatment and bedside decision making [23]. The results of a new study by He et al indicate that elevated IL-27 strongly correlates with ENS and may provide additional diagnostic value along with procalcitonin [24].…”
Section: Cytokines As Sepsis Biomarkersmentioning
confidence: 99%